Water quality at the source and incidence of water borne diseases in rural households of South India - Jayakrishnan, Thayyil; Rao, Bhaskar; Cyriac, Milu Elizabath; Harikumar, P. S.; Cherumanalil, Jeeja Mathummal (International Journal Of Community Medicine And Public Health, 2021)
Background: The relation of water quality indicators and water borne diseases (WBD) is not properly studied in tropical countries like India. Most of the studies done were cross sectional which reported only point prevalence. This tends to under-estimate and is not adequate to explain the relation. In this context to assess the incidence of water born diseases in relation to household drinking water quality, a longitudinal prospective study was conducted. Methods: The study was conducted in a South Indian state, in a rural area among the members of 300 households by weekly data collection for one year. Water samples were collected and analysis was done thrice corresponding to the climate. Bacterial quality indicators - Total coliform count (TCC), Faecal coliform count (FCC) and E. coli were estimated. The data were processed and analyzed. Results: From 300 households, total 1459 persons were enrolled. During the 12 months period, 72 episodes of WBDs were recorded with incidence rate of 49/1000 person years. Proportional morbidity due to WBD was 11.9%. The WBD reported were ADD, dysentery and hepatitis A. Up to 30% water sources contained E. coli in summer and winter samples and more than 60% in rainy samples. Faecal coliform count was >10 MPN/100 ml in all the seasons in more than 60% water sources Conclusions: Most of the main water source wells were contaminated. Contamination was more in rainy season. Incidence of WBD has no correlation with water quality indicators in all the seasons (p≥0.05).